Cutting tool wear analysis using sound signal and simple microphone. Issue 4 (April 2020) - Huda, F; Karjuni, K; Rusli, M
Abstract: Cutting tool is an important part of machining processes which in the operation frequently runs into wear. The wear cutting tool produces an imprecise product with low quality surface, may endanger machine tools by stimulating chatter. In this study, low cost and fast analysis of the wear of cutting tools in turning and drilling processes are proposed. For that purpose, the experimental set-up which consists of operating turning and drilling machine, simple microphone and Personal Computer (PC) with a sound card are set out. The wear of cutting tools are made by applying artificial wear. The sound data from normal and wear cutting tools of operating turning and drilling machines are recorded by using simple microphone and PC with a sound card. The obtained sound signals are then analyzed in the form of time and frequency domain, spectrogram by Wavelet Transform (WT). It is found that sound signals in time and frequency domain have a significant rise of amplitudes in wear conditions. The spectrograms exhibit the special contours which sign the existence of wear. The results demonstrate that the proposed method can analyze the cutting tool wear very well.